Delivering nutrient management impact through farmer-centric research: a systematic review of innovation systems in African smallholder systems - Adolwa, Ivan S.; Zingore, Shamie; Mutegi, James; McNee, Matthew; Akorede, Bolaji A.; Masidza, Denver; Murrell, T. Scott; Ndungu, Samuel Mathu; Nchanji, Eileen; Cook, Simon; Oberthür, Thomas (Elsevier, 2025)
CONTEXT: The performance of the agricultural sector in Africa still lags behind other regions. The current average maize productivity of 2 t ha-1 is below the global average of about 6 t ha-1. This low productivity threatens the livelihoods of a majority of the population. Despite decades of research and development investments, current agricultural innovation systems remain ineffective in supporting sustainable agricultural transformation. OBJECTIVE: This study traces the evolution of innovation systems in Africa as a backdrop to the adaptation of on-farm experimentation (OFE), which is a novel framework for accelerating research and development (R&D) impact. METHODS: A systematic review approach is augmented with social network analysis methods and primary and secondary data. RESULTS AND CONCLUSIONS: We find that although current innovation systems have contributed to enhancing co-learning processes and have enabled the partial adoption of improved agronomic practices, resulting in increased nutrient uptake efficiency and crop productivity, several shortcomings have limited their impact. Despite their core focus on participatory and systemic R&D processes, our review points to their inability to effectively engage farmers. Hence, failing to generate scalable learning, and demonstrate sufficient value to farmers and other stakeholders. The OFE initiatives demonstrate how farmer-relevant insights integrated with field-based and digital evidence help spur a farmer-driven innovation development and decision support framework. SIGNIFICANCE: OFE is potentially a powerful enabler of current innovation systems performance as it provides the platform for a transformative farmer-led innovation process.